PENGARUH LINGKUNGAN KERJA, KOMPENSASI, MOTIVASI INTRINSIK DAN KEPEMIMPINAN DEMOKRATIS TERHADAP LOYALITAS KARYAWAN - Zunaidi, Zunaidi; Prayekti, Prayekti; Septyarini, Epsilandri (STKIP Persada Khatulistiwa Sintang, 2023)
Human resources can be said to be internal suppliers who play a very important role in producing goods or services. The loyalty of employees in an organization is absolutely necessary for the success of the organization itself. Having quality human resources and having high loyalty to the company can empower its resources effectively, efficiently and productively. This research aims to determine the influence of democratic leadership style, intrinsic motivation, compensation and work environment on employee loyalty. This research is quantitative. The population in the study was 50 employees. The sampling technique used in this research was a saturated sample (census). Data were collected using a questionnaire, data were analyzed using validity and reliability tests, multiple linear regression, classical assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests, T-tests and F-tests. From the results of this research, the work environment influences employee loyalty. Compensation has no significant effect on the employee loyalty variable. Intrinsic motivation influences employee loyalty. Leadership style influences employee loyalty. Simultaneously, the influence of the work environment, compensation, intrinsic motivation and democratic leadership on employee loyalty has a positive and significant effect.